2019
DOI: 10.1002/ijc.32326
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing reveals PNN and KCNQ1OT1 as predictive biomarkers of clinical outcome in stage III colorectal cancer patients treated with adjuvant chemotherapy

Abstract: Five‐year overall survival of stage III colorectal cancer (CRC) patients treated with standard adjuvant chemotherapy (ACHT) is highly variable. Genomic biomarkers and/or transcriptomic profiles identified lack of adequate validation. Aim of our study was to identify and validate molecular biomarkers predictive of ACHT response in stage III CRC patients by a transcriptomic approach. From a series of CRC patients who received ACHT, two stage III extreme cohorts (unfavorable vs. favorable prognosis) were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…Although our sensitivity analysis revealed that the results only (Sun et al 2017) impacted the outcomes, the overall heterogeneity was low in our included studies. These results are consistent with the findings of previous studies [12]. Indeed, there are several limitations to this study that should be pointed out.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Although our sensitivity analysis revealed that the results only (Sun et al 2017) impacted the outcomes, the overall heterogeneity was low in our included studies. These results are consistent with the findings of previous studies [12]. Indeed, there are several limitations to this study that should be pointed out.…”
Section: Discussionsupporting
confidence: 94%
“…Recent studies have indicated that lncRNA KCNQ1OT1 participates in various biological processes, such as cell proliferation, apoptosis, and drug resistance [7][8][9]. In addition, lncRNA KCNQ1OT1 is involved in the progression of different cancers, including breast carcinoma [10], CRC [8,11,12], tongue carcinoma [13], lung carcinoma [14], and stomach carcinoma [15]. The clinicopathological characteristics, including overall survival, lymphatic meta-stasis, TNM stage, and tumor size, are also positively correlated with lncRNA KCNQ1OT1 expression levels in cancers [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Such as, knockdown ANO1 expression could increase the apoptosis effects induced by L-OHP and 5-FU [26]. Moreover, RNA sequencing revealed PNN could be a predictive biomarker of clinical outcome in stage colorectal cancer patients treated with L-OHP and 5-Fu chemotherapy [27]. Additionally, it was reported that LEF1 was associated with 5-FU [28] and L-OHP caused bending of DNA produced targets for LEF1-binding [29].…”
Section: Discussionmentioning
confidence: 99%
“…By specific binding with RALY, RALYL could inhibit the oncogenic effects of RALY. Furthermore, HNRNPC, CRNKL1, PNN and PPIE were also reported to have a high expression and biological function in several cancers including ovarian cancer [21][22][23][24]. RALYL might also play the anti-tumor effects by suppressing these oncogenic genes.…”
Section: Discussionmentioning
confidence: 99%